A critique of clinical economy: reassessing value and care during covid-19—an essay by Eric Reinhart and Daniel Brauner. (27th July 2020) - Reinhart, Eric; Brauner, Daniel
Abstract : For decades, American medical practice has been organised around billing codes, with severe consequences for patient care and physician morale. The interruption of routine clinic visits owing to covid-19 presents an opportunity to reconsider the guiding principles of clinical care, write Eric Reinhart and Daniel Brauner